Perbandingan Hasil Belajar IPA-Biologi Menggunakan Model Brain Based Learning Menggunakan Peta Konsep Dengan Metode Diskusi Pada Siswa Kelas VII SMP Negeri 22 Surakarta - Fitriana, Elda; Dr.Sofyan Anif, Dr.Sofyan Anifn,M.Si (2016)
The aims of this research is to know the comparison of IPA-Biology learning outcome between the application of Brain Based Learning method using concept map with discussion method for the VII grade students at SMP Negeri 22 Surakarta. The type of this research is experiment research.the design of this research is ex post facto. The taking of sample was done by random sampling. The sample of this research is the students of VII B class as the first treatment class and the students of VII E class as the second treatment class. The techniques of collecting data is posttest. The techniques of analyzing data is one way anova. The result of analyzing data is gained the probability value to the students learning outcome is 0,00 < 0,05 so H0 is refused, it means that there is the difference of the average of the students learning outcome for the first treatmen class with the second treatment class. It can be seen from the average of the first treatment class is 79,83, meanwhile the second treatment class is 71,25. Hence, it can be concluded that the application of brain Based Learning model using concept map has the IPA-Biology learning outcome is better than the application of discussion method. Key words: Brain Based Learning model, concept map media, discussion method, students learning outcome.